Teachers’ Perspectives and Practices in Implementing Mathematical Literacy-Oriented Learning - Udil, Patrisius Afrisno; Nurlaelah, Elah; Jupri, Al (RANGE: Jurnal Pendidikan Matematika, 2025)
Teachers’ understanding and implementation of mathematical literacy-oriented learning are crucial for enhancing students' mathematical literacy. A growing body of research have been conducted to improve students’ mathematical literacy, particularly focused on studying and understanding students’ obstacle and how to facilitate the issues. On the other hand, there have been limited studies concerned on understanding teachers’ role in promoting students’ mathematical literacy. This study aims to analyze teachers’ perspectives and practices in designing and implementing learning treatments for enhancing students’ mathematical literacy. A qualitative method with a case study is carried out in this research. Subjects in this research consist of 6 mathematics teachers (2 junior high school teachers and 4 senior high school teachers) at Kupang, East Nusa Tenggara Province, Indonesia. Data collection techniques in this study were conducted using interviews, observation, and documentation. The data were analyzed qualitatively based on the data obtained from the research instruments by reducing data, presenting data, and concluding/ verification. The result of the study indicates that teachers believe their knowledge of mathematical literacy is good and claim to be able to design and implement mathematical literacy-oriented learning well. However, document analysis, observations, and interviews with respondents indicated that teachers’ knowledge and skills to design and implement mathematical literacy-oriented learning still need to be improved. A specific characteristic of teachers’ lack of knowledge and skills in designing and implementing mathematical literacy-oriented learning is discussed in this study.